Nation in Spite of Forms: A Poetic Construction of the Republic (2014)
The purpose of this article is to highlight the role of poetry as an essential element in the project of independence, both as an instrument responsible for the creation of the new emancipated reality, on one hand, and of a concept of nation based on a re